Z-score Analysis for Financial Stability on Real Estate Companies in the Indonesian Stock Exchange - Herry Santoso (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main purpose: This study empirically investigates the influence of Profitability (PRFT), Leverage (LEVG), Liquidity (LIQD), Firm Age (FAGE), Interest Rate (INTR), Firm Value (FVAL), Firm Size (FISZ), and the COVID-19 pandemic (COVD) on the Financial Stability (FSTA) of real estate companies listed on the Indonesia Stock Exchange during the period 2012–2022. Method: The research utilizes secondary data and applies a purposive sampling method to select samples based on predefined criteria, drawing from a population of 83 registered real estate firms. Main Findings: The findings indicate that the independent variables collectively have a significant effect on FSTA. However, the individual significance tests reveal that in Model 1, PRFT and COVD do not significantly impact FSTA, while in Model 2, INTR and COVD show no significant effect on FSTA. Theory and Practical Implication: The study highlights the applicability of the trade-off and pecking order theories in explaining how real estate firms strategically manage profitability, leverage, and liquidity to sustain financial stability. Novelty: This study uniquely examines the interplay between capital structure and financial indicators during the COVID-19 pandemic, providing empirical insights specific to Indonesia’s real estate sector—an area that has received limited scholarly attention.